2011
DOI: 10.1021/cb200287c
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Form Matters: Differential Accumulation of Mercury Following Inorganic and Organic Mercury Exposures in Zebrafish Larvae

Abstract: Mercury, one of the most toxic elements, exists in various chemical forms each with different toxicities and health implications. Some methylated mercury forms, one of which exists in fish and other seafood products, pose a potential threat, especially during embryonic and early postnatal development. Despite global concerns, little is known about the mechanisms underlying transport and toxicity of different mercury species. To investigate the impact of different mercury chemical forms on vertebrate developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
120
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(125 citation statements)
references
References 43 publications
5
120
0
Order By: Relevance
“…After a 48 hour exposure all fish were rinsed 3 times in fresh system water to remove excess mercury on the surface of the fish. Zebrafish were fixed, embedded and sectioned as previously described [7].…”
Section: Xfi Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…After a 48 hour exposure all fish were rinsed 3 times in fresh system water to remove excess mercury on the surface of the fish. Zebrafish were fixed, embedded and sectioned as previously described [7].…”
Section: Xfi Sample Preparationmentioning
confidence: 99%
“…Data collected from X-ray fluorescence imaging were processed as previously described [7], with normalization to the incoming beam intensity and removal of background signal by averaging the intensity per element in the area outside of the tissue then subtracting this amount from each pixel in the entire image. Certified highly-uniform thin film standards mounted on 6.3 μm Mylar substrates for zinc, gold, and thallium were obtained from Micromatter Co. (Vancouver, BC).…”
Section: Xfi Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that high levels of mercury exposure may occur via the use of skin lightening beauty creams, soaps and herbal drugs 3,4 . The toxic effects of mercury vary with the different chemical forms of mercury, the dose and the rate of exposure 2,5 .…”
Section: -Introductionmentioning
confidence: 99%
“…[6] For all toxic heavy metals, which undergo physical and/or chemical transformations, the total concentration of an element in general cannot reflect the hazard or benefit of their individual species. Korbas et al [7] studied the difference in toxicity between OrgHg and inorganic Hg species towards Zebrafish larvae and demonstrated that OrgHg resulted in overall higher Hg burdens and also targeted different cells and tissues than their inorganic counterparts. This indicates that the toxicity depends on the chemical forms of an element than its total quantity.…”
Section: Sample Preservation and Storagementioning
confidence: 99%